A function f is defined over the set of all positive integers and satisfies : f ( 1 ) = 1 9 9 6 ∀ n > 1 k = 1 ∑ n f ( k ) = n 2 f ( n ) Calculate the value of f ( 1 9 9 6 ) , if it is b a , g cd ( a , b ) = 1 then submit a + b
S o u r c e : B r i t i s h M a t h e m a t i c s O l y m p i a d R o u n d 1 1 9 9 6 P r o b l e m 2
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Observation :
n | f ( n ) | ∑ k = 1 n f ( k ) |
1 | 1 1 9 9 6 | 1 1 9 9 6 × 1 |
2 | 3 1 9 9 6 | 3 1 9 9 6 × 4 |
3 | 6 1 9 9 6 | 4 1 9 9 6 × 6 |
4 | 1 0 1 9 9 6 | 5 1 9 9 6 × 8 |
5 | 1 5 1 9 9 6 | 6 1 9 9 6 × 1 0 |
6 | 2 1 1 9 9 6 | 7 1 9 9 6 × 1 2 |
C o n j e c t u r e : f ( n ) = 2 n ( n + 1 ) 1 9 9 6 = n ( n + 1 ) 1 9 9 6 × 2 P r o o f : f ( 1 ) = 1 × ( 1 + 1 ) 1 9 9 6 × 2 = 1 9 9 6 . . . . . . . . . . [ 1 ] k = 1 ∑ n f ( k ) = k = 1 ∑ n k ( k + 1 ) 1 9 9 6 × 2 1 9 9 6 × 2 k = 1 ∑ n k ( k + 1 ) ( k + 1 ) − k 1 9 9 6 × 2 k = 1 ∑ n k ( k + 1 ) k + 1 − 1 9 9 6 × 2 k = 1 ∑ n k ( k + 1 ) k = 1 9 9 6 × 2 k = 1 ∑ n k 1 − 1 9 9 6 × 2 k = 1 ∑ n k + 1 1 = 1 9 9 6 × 2 k = 1 ∑ n k 1 − 1 9 9 6 × 2 k = 2 ∑ n + 1 k 1 = 1 9 9 6 × 2 ( 1 − n + 1 1 k = 2 ∑ n k 1 − k = 2 ∑ n k 1 ) = 1 9 9 6 × n + 1 2 n = 1 9 9 6 × ( n + 1 ) × n 2 n × n = 1 9 9 6 × ( n + 1 ) n 2 n 2 = n 2 × n ( n + 1 ) 1 9 9 6 × 2 = n 2 f ( n ) Q . E . D . f ( 1 9 9 6 ) = 1 9 9 6 × ( 1 9 9 6 + 1 ) 1 9 9 6 × 2 = 1 9 9 7 2 ∵ g cd ( 2 , 1 9 9 7 ) = 1 ∴ A n s w e r = 1 9 9 7 + 2 = 1 9 9 9
n is strictly greater than 1, please remove the 1st row from your observation table to make it precise.
Log in to reply
The question says that ∀ n > 1 f ( n ) = n 2 f ( n ) It doesn't say that n = 1 ⇒ f ( n ) = n 2 f ( n )
Problem Loading...
Note Loading...
Set Loading...
f ( 1 ) f ( 1 ) + f ( 2 ) f ( 1 ) + f ( 2 ) + f ( 3 ) f ( 1 ) + f ( 2 ) + f ( 3 ) + f ( 4 ) k = 1 ∑ n f ( k ) − k = 1 ∑ n − 1 f ( k ) ⟹ f ( n ) ⟹ f ( n ) = 1 2 f ( 1 ) = 2 2 f ( 2 ) ⟹ f ( 2 ) = 3 1 f ( 1 ) = 3 2 f ( 3 ) ⟹ f ( 3 ) = 8 4 f ( 2 ) = 8 4 3 1 f ( 1 ) = 4 2 f ( 4 ) ⟹ f ( 4 ) = 1 5 9 f ( 3 ) = 1 5 9 8 4 3 1 f ( 1 ) = n 2 f ( n ) − ( n − 1 ) 2 f ( n − 1 ) = n 2 f ( n ) − ( n − 1 ) 2 f ( n − 1 ) = n 2 − 1 ( n − 1 ) 2 f ( n − 1 ) = n + 1 ( n − 1 ) f ( n − 1 )
So, we have, for n ≥ 2
f ( n ) = k = 2 ∏ n n + 1 n − 1 f ( 1 ) = ( n + 1 ) n 2 f ( 1 )
∴ f ( 1 9 9 6 ) = 1 9 9 7 1 9 9 5 1 9 9 6 1 9 9 4 1 9 9 5 1 9 9 3 . . . 4 2 3 1 f ( 1 ) = 1 9 9 7 × 1 9 9 6 2 × 1 9 9 6 = 1 9 9 7 2
Hence, a + b = 2 + 1 9 9 7 = 1 9 9 9